The Meaning of Spirituality to Person with Schizophrenia: A Hermeneutic Inquiry - Cavey, Ann Nina (My University, 2009)
This study sought to explore the meaning of spirituality to individuals living with schizophrenia. Gadamer's philosophy of understanding underpinned this hermeneutic inquiry. The study took place in a community-based psychosocial rehabilitation program in an urban Canadian setting. The sample included 7 English-speaking men and women, ages 25 to 49, who had not been hospitalized for six months or more. Methods involved hermeneutic analysis of verbatim transcripts of open-ended individual interviews. Four major themes were identified: the fractured self: the meaning of a "spiritual holocaust"; the vortex: the meaning of a subverted spirituality; the emergent self: the meaning of spiritual cohesion; and the nurtured self: the meaning of spiritual practices. Findings demonstrated the high value ascribed to spirituality in the lives of participants, regardless of whether they had a religious affiliation. Spirituality was seen as the fundamental connecting force that maintains the integrity of the self against the fragmenting effects of the illness. Participants felt this connectedness could be profoundly challenged as spirituality interacts with delusions. Nevertheless, spiritual connections within the individuals' life stories, with their community and with God provided the stability that helped them develop a robust sense of self while living with the illness. Implications for practice include the need to courageously support consumers in their spiritual meaning- making. Research recommendations encourage replication of this study in a more diverse population in terms of religious affiliation and an exploration of the spiritual meaning of music and art to persons with major mental illness.
Keywords: Medicine and Health Sciences; Nursing; Medicine and Health Sciences